Fundamentos para una justicia deportiva en un contexto de Estado de Derecho - Pugliese, Blas (2026)
This article analyzes the foundations of sports justice in the context of the rule of law. It examines the relationship between the state legalsystem and the multiple private legal systems of sport, highlighting how the state allows and limits the regulatory autonomy of sports institutions.It also addresses the production of sports rules, their coexistence with state law, and the scope of judicial control over sports justice.Finally, it emphasizes the need to reconcile autonomy and legality in order to guarantee the validity of the sports system in harmony with stateprinciples.